Workplace positive actions, trans people's self-esteem and human resources' evaluations. Issue 6 (12th November 2019) - Bozani, Vasiliki; Drydakis, Nick; Sidiropoulou, Katerina; Harvey, Benjamin; Paraskevopoulou, Anna
Abstract : Purpose: The purpose of this paper is to provide empirical patterns regarding trans people's self-esteem-oriented evaluations during observations of positive workplace actions. The case of a 2015 UK workplace guide is utilized to fulfil the aims. The guide provides suggestions to employers for recruiting and retaining trans people. Design/methodology/approach: A new questionnaire is created which forms a 20-item scale capturing a variety of self-evaluations. Trans people provided their responses in a 2018–2019 survey and the study's patterns were captured. Findings: The outcomes suggest that trans people's self-esteem and self-respect are enhanced by policy makers' positive actions to promote inclusivity in the workplace. In addition, due to these actions trans people feel more accepted, valued and trusted by the government. The authors suggest that a lack of positive workplace actions may be detrimental to trans people's self-esteem. However, if a workplace policy is perceived to be a recognition of trans people's worth this may be internalized, resulting in positive self-evaluations. The authors suggest that the 2015 workplace guide aims to ensure that trans people's self-expressions are not constrained in ways that could cause them self-esteem difficulties. Practical implications: The study also finds that firms which have implemented the workplace guide have informed human resources strategies, affected corporate profiles and staff organizational behaviours, created a more inclusive workplace culture, and addressed LGBT business and trans staff members' needs. The authors suggest that when employers utilize policy makers' positive workplace policies they may be able to realize positive organizational outcomes in their firms. Social implications: The World Health Organization perceives self-esteem as a public matter and this study suggests that inclusive workplace strategies can positively affect the psychological states of a highly marginalized population group. Originality/value: To the best of the authors' knowledge this is the first attempt to quantify how a workplace guide impacts on self-esteem-oriented evaluations among trans people. Each one of the 20 items in the scale brings new insights into the subject matter.